Efektivitas Desa Wisata Dalam Peningkatan Ekonomi Sebagai Upaya Perwujudan Desa Mandiri Budaya di Kalurahan Bejiharjo - Aprelia, Evi; Nugroho, Hanantyo Sri (Faculty of Social and Political Science, Universitas Siliwangi, 2025)
This research examines the effectiveness of the tourism village program in improving the economy as an effort to create an Independent Cultural Village in Bejiharjo Village, Karangmojo District, Gunungkidul Regency. The Tourism Village Program in Bejiharjo Village aims to improve the community's economy through developing local tourism potential, which is integrated with cultural values and local wisdom. Through this program, local communities are involved in various economic activities, such as providing tourism services, handicrafts and culinary businesses so that they can increase the economic income of the surrounding community. Efforts to improve the economy are carried out through increasing community skills in tourism management, promoting local products, as well as developing tourism supporting facilities and infrastructure. By combining the tourism village program and cultural preservation, it is hoped that it will be able to create an independent community. This research uses qualitative descriptive methods, data collection techniques for this research use observation, interviews and documentation techniques. In this discussion, researchers use Duncan's effectiveness theory, there are three indicators to measure effectiveness, including goal achievement, integration and adaptation.